2008
DOI: 10.1093/nar/gkn880
|View full text |Cite
|
Sign up to set email alerts
|

Efficient processing of TFO-directed psoralen DNA interstrand crosslinks by the UvrABC nuclease

Abstract: Photoreactive psoralens can form interstrand crosslinks (ICLs) in double-stranded DNA. In eubacteria, the endonuclease UvrABC plays a key role in processing psoralen ICLs. Psoralen-modified triplex-forming oligonucleotides (TFOs) can be used to direct ICLs to specific genomic sites. Previous studies of pyrimidine-rich methoxypsoralen–modified TFOs indicated that the TFO inhibits cleavage by UvrABC. Because different chemistries may alter the processing of TFO-directed ICLs, we investigated the effect of anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…However, the UvrA expression level of L. lactis increased slightly as heat stress continued. It seems that UvrA plays an important role in assisting the organism's adaptation to heat stresses, possibly by protecting proteins from denaturation (Christensen et al 2008). Our data shown that over expression of UvrA and exposed to heat treatment significantly enhances the growth performance and survival rate of L. lactisUvrA.…”
Section: Discussionmentioning
confidence: 54%
“…However, the UvrA expression level of L. lactis increased slightly as heat stress continued. It seems that UvrA plays an important role in assisting the organism's adaptation to heat stresses, possibly by protecting proteins from denaturation (Christensen et al 2008). Our data shown that over expression of UvrA and exposed to heat treatment significantly enhances the growth performance and survival rate of L. lactisUvrA.…”
Section: Discussionmentioning
confidence: 54%
“…A report by Guieysse et al (2000) confirmed this mechanism of triplex-mediated incision inhibition. However, a more recent study from the Vasquez Laboratory (Christensen et al, 2008) suggests that triplex formation does not inhibit the incision site at which the TFO is bound to and is further accessed by UvrABC nucleases. A more detailed study on a variety of DNA mutations revealed that the frequency of deletions is independent on ERCC1-XPF and TCR activity.…”
Section: Kolevzon and Yavinmentioning
confidence: 98%
“…In bacteria, a psoralen ICL (Van Houten et al, 1986) and a psoralen ICL directed by a triplex-forming oligonucleotide (Christensen et al, 2008) can be repaired by dual incision via the NER pathway. It is possible that this also occurs in mammalian cells.…”
Section: Biological Functions Of Ercc1-xpfmentioning
confidence: 99%